Principal Management in Optimizing the Implementation of G7kaih to Realize A School Culture With Character In Paud Kindergarten Aisyiyah 1 Rancaekek Bandung Regency - Sri Sumarni; Eva Dianawati Wasliman (International Journal of Education, Information Technology, and Others, 2026)
Early character education is crucial, especially during a child's golden age (0–6 years). Due to challenges like moral decline and negative environmental factors, Early Childhood Education (PAUD) institutions need programs that are structured and continuous. This study aims to analyze how principals manage the Seven Habits of Great Indonesian Children (G7KAIH) program using the POAC cycle (Plan- Organizing-Actuating-Controlling) to create a strong character culture within the school. The Seven Habits Program covers seven main habits: waking up early, worshiping, exercising, eating healthy food, loving to learn, interacting socially, and sleeping early. The goal is to develop highly capable individuals with strong character. We used a descriptive qualitative approach for this research at PAUD TK Aisyiyah 1 Rancaekek, which has run The Seven Habits Program since 2023. The result show that implementing The Seven Habits Program positively affects students’ character, increasing their independence, discipline, and social care. The main analysis will focus on how the principal's planning, execution, evaluation, and follow-up successfully integrate The Seven Habits Program systematically and fully into the school environment